2014
DOI: 10.1007/978-1-4939-1601-6_1
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Ramanujan Primes

Abstract: In 1845, Bertrand conjectured that for all integers x ≥ 2, there exists at least one prime in (x/2, x]. This was proved by Chebyshev in 1860, and then generalized by Ramanujan in 1919. He showed that for any n ≥ 1, there is a (smallest) prime R n such that π(x) − π(x/2) ≥ n for all x ≥ R n . In 2009 Sondow called R n the nth Ramanujan prime and proved the asymptotic behavior R n ∼ p 2n (where p m is the mth prime). He and Laishram proved the bounds p 2n < R n < p 3n , respectively, for n > 1. In the present pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Remark. Amersi, Beckwith, Miller, Ronan and Sondow [1] showed that there exists a positive constant c = c(k) such that…”
Section: On the Difference Kn Log Rmentioning
confidence: 99%
See 4 more Smart Citations
“…Remark. Amersi, Beckwith, Miller, Ronan and Sondow [1] showed that there exists a positive constant c = c(k) such that…”
Section: On the Difference Kn Log Rmentioning
confidence: 99%
“…Let π k (x) be the number of k-Ramanujan primes less than or equal to x. Amersi, Beckwith, Miller, Ronan and Sondow [1] proved that…”
Section: On the Number Of K-ramanujan Primes ≤ Xmentioning
confidence: 99%
See 3 more Smart Citations